Clinical outcomes with canagliflozin according to baseline body mass index: results from post hoc analyses of the CANVAS Program. Issue 4 (3rd January 2020) - Ohkuma, Toshiaki; Van Gaal, Luc; Shaw, Wayne; Mahaffey, Kenneth W.; de Zeeuw, Dick; Matthews, David R.; Perkovic, Vlado; Neal, Bruce
Abstract: Aims: Sodium glucose co‐transporter 2 (SGLT2) inhibitors reduce several cardiovascular risk factors, including plasma glucose, blood pressure, albuminuria and body weight. Long‐term treatment lowers risks of cardiovascular and renal events. The objective of this post hoc analysis was to determine the effects of canagliflozin treatment versus placebo on clinical outcomes in relation to body mass index (BMI). Materials and methods: The CANVAS Program randomized 10 142 participants with type 2 diabetes to canagliflozin or placebo. These analyses tested the consistency of canagliflozin treatment effects across BMI levels for cardiovascular, renal, safety and body weight outcomes in three groups defined by baseline BMI: <25, 25‐<30 and ≥30 kg/m 2 . Results: In total, 10 128 participants with baseline BMI measurements were included. There were 966 participants with BMI <25 kg/m 2, 3153 with BMI 25‐<30 kg/m 2 and 6009 with BMI ≥30 kg/m 2 . Mean percent body weight reduction with canagliflozin compared with placebo was greater at 12 months [−2.77% (95% confidence interval (CI): −2.95, ‐2.59)] than at 3 months [‐1.72% (95% CI: ‐1.83, ‐1.62)]. The hazard ratios (HRs) for canagliflozin compared with placebo control for the composite outcome of cardiovascular death, non‐fatal myocardial infarction or non‐fatal stroke were 1.03 (95% CI: 0.66, 1.59) in participants with BMI <25 kg/m 2, 0.97 (0.76, 1.23) with BMI 25‐<30 kg/m 2 and 0.79 (0.67, 0.93) with BMI ≥30 kg/m 2 ( P for heterogeneity = 0.55). The effects of canagliflozin on each component of the composite were also similar across BMI subgroups, as were effects on heart failure and renal outcomes ( P for heterogeneity ≥0.19). The effects on safety outcomes were also broadly similar. Conclusions: Canagliflozin improved cardiovascular and renal outcomes consistently across patients with a broad range of BMI levels.